LOCAL POLITICS AND DEMOCRACY ON POLICY IMPLEMENTATION IN MADURA - Wilda Rasaili (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2023)
Policy implementation is very dominant in determining the success of the policy. The success of the policy is 60% determined by the implementation of the policy, planning, and evaluation of each 20%. However, in its application, the concept of policy implementation triggers a revitalization debate related to the development of democratic orientation and post-positivist methods. a concept that was born and developed in Latin America and the West is not easy to apply in developing countries. The political environment and sectoral social conditions determine the optimization of policy implementation. so that selective policy implementation is needed. The purpose of this study is to explain the influence and importance of democracy and local politics on policy implementation in the Madura region. The approach used is qualitative with primary and secondary data collection through interviews, observations, documentaries, and FGDs. Data analysis uses the Miles and Huberman model, namely data reduction, data display, and verification. The results show that the concept of policy implementation is closely related to the political and democratic environment. Local political conditions and the running of democracy affect the optimization of policy implementation. The dynamics of democracy in the Pilkada in the Madura Region are still elitist which results in weak public participation and the strengthening of basic food and money politics. Public gatherings, mass media, political parties, and civil liberties also do not serve to encourage accommodation of the public interest in policy and policy implementation. So that local politics which is marked by weak democracy in the Madura region has implications for the low quality of policy implementation.